Mission Report: The experience of the Local Public Health Service of Reggio Emilia (Italian Journal of Public Health, 2008)
Background: The Mission Report’s purpose is to give an account to the main institutional stakeholders ( the Region and the Territorial Health and Social Conferences, composed of the mayors of the provincial municipalities, the General Directors of the Local Public Health Services in the provincial territory and are chaired by the Chairman of the Province) of how the Local Public Health Service, through an effective and efficient use of resources, has answered the health needs of the resident population of the province. Other stakeholders include public health service employees of the local community, associations, and partners.Methods: The Local Public Health Service (L’Azienda USL) of Reggio Emilia has produced annual Mission Reports since 2005. Three editions of the document have therefore been published, reporting results achieved in 2004, 2005 and 2006; the Mission Report for 2007 is currently in the editorial phase. The various sections of the document take the reader from an analysis of the local context in which the Local Public Health Service operates (territory and environment, demographic indices, socio-economic conditions, morbidity and mortality, lifestyle, safety) to the health and social services provided throughout the province. The strategies employed to achieve health outcomes are illustrated following the indications of the Region. The Mission Report opens with an introduction and closes with concluding remarks from the General Director. These remarks include both an assessment of the year’s activity and the main points that will guide future planning.Discussion: Local Public Health Service of Reggio Emilia sees the Mission Report as a management tool: the analysis of the provincial demographic context and the socio-economic conditions of the population direct the Public Health Service’s choice of which health and social services to provide. In the interest of transparency, particular attention is paid to how topic points are expressed; even the non-expert reader can follow the clear and comprehensible presentation of data.Conclusions: Our experience has been positive. The document has allowed us to direct our planning through a careful analysis of the health and social needs of the population thanks to an annual monitoring of numerous indicators, which are interpreted throughout the Emilia Romagna Region in the same way. This makes benchmarking with the other provinces possible, in an effort to constantly improve the quality of services provided.
Keywords: mission report; accountability; health community; health communication